Pelvic Ectopic Kidney in an Adult: Robotic-Assisted Surgical Treatment of Unrecognized Ureteropelvic Junction Obstruction - Amr Ahmed; Aleksa Zubelic; Milan Radovanovic; Gjoko Stojanoski; Jerome Katz (Case Reports in Surgery)
Ureteropelvic junction obstruction (UPJO) is observed in approximately 30% of patients with ectopic kidneys. Due to the narrow pelvic space and risk of injuring aberrant structures, an ectopic pelvic kidney with UPJO presents a unique treatment challenge. Most experiences in treating UPJO in pelvic ectopic kidneys using robotic surgical systems are based on the pediatric population. Only a few cases of successful robotic-assisted surgery in adult patients with this condition have been described. This case reports illustrates that the indications for robotic-assisted surgery for UPJO may safely be expanded to include complex adult cases with pelvic ectopic kidney.